2020
DOI: 10.3390/plants9121782
|View full text |Cite
|
Sign up to set email alerts
|

HTS-Based Monitoring of the Efficiency of Somatic Embryogenesis and Meristem Cultures Used for Virus Elimination in Grapevine

Abstract: Meristem culture and somatic embryogenesis are effective tools for virus elimination of vegetatively propagated crops including grapevine (Vitis vinifera L.). While both have been shown to be useful to eliminate the main grapevine viruses, their efficiency differs depending on the virus and grapevine variety. In our work, we investigated the efficiency of these two virus elimination methods using small RNA high-throughput sequencing (HTS) and RT-PCR as virus diagnostics. Field grown mother plants of four clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…In library 007 ("Rebula" variety) all eight samples were infected, while in library 014 ("Malvazija" variety) only two samples were infected. In Hungary, using sRNA-seq approach, the same contradictory results were reported by three independent studies (Czotter et al, 2018;Demian et al, 2020;Turcsan et al, 2020). The authors indicated that this could be due to technical issues, the possibility that concentrations were under detection threshold due to the bulk sequencing strategy or deeper biological aspects, as a possible long coexistence between grapevine and GRSPaV resulted in mutual adaptation (Gambino et al, 2012), and potentially the plant immune response was not activated.…”
Section: Grapevine Rupestris Stem Pitting-associated Virusmentioning
confidence: 82%
“…In library 007 ("Rebula" variety) all eight samples were infected, while in library 014 ("Malvazija" variety) only two samples were infected. In Hungary, using sRNA-seq approach, the same contradictory results were reported by three independent studies (Czotter et al, 2018;Demian et al, 2020;Turcsan et al, 2020). The authors indicated that this could be due to technical issues, the possibility that concentrations were under detection threshold due to the bulk sequencing strategy or deeper biological aspects, as a possible long coexistence between grapevine and GRSPaV resulted in mutual adaptation (Gambino et al, 2012), and potentially the plant immune response was not activated.…”
Section: Grapevine Rupestris Stem Pitting-associated Virusmentioning
confidence: 82%
“…Smerea et al (2010) reported that the healthy status of grapevine also affected the meristem regeneration capacity. Turcsan et al (2020) concluded that the meristem culture was a difficult technique as the regeneration capacity of the shoot tips bigger than 0.5 mm is higher but extra length also increase the virus level.…”
Section: Resultsmentioning
confidence: 99%
“…Meristem culture-based elimination could not 100% eliminate GRSPaV or GVT, which could explain their almost even distribution in the infected cultivars. However, chemotherapy and somatic embryogenesis-based methods gave better results for GRSPaV and for both viruses, which could be optimized in the future if new regulations target foveaviruses [16,18].…”
Section: Discussionmentioning
confidence: 99%